PENGARUH JENIS BAHAN ORGANIK DAN KONSENTRASI Azotobacter sp TERHADAP PERTUMBUHAN SEMAI JATI (Tectona grandis Linn. F) - s, Syaifuddin; m, Muslimin (Universitas Tadulako, 2019)
Azotobacter is a non-symbiotic bacterium and can capture N in the air. Azotobacter lives as heterotrophic bacteria that need organic as food. Azotobacter has the potential to developed in Teak plants, considering that Teak is not from legume. This study aims to types of organic and the concentration Azotobacter sp on the growth of Teak plants (Tectona grandis Linn. F). The study conducted three months from January to March 2019, which conducted at the Temporary Nursery Area of the Faculty of Forestry, Tadulako University. This study uses a Completely Randomized Design (CRD) factorial pattern with two factors consisting of organic matter factors, without organic matter (B0), straw (B1), goat manure (B2), and cocoa skin (B3), the second factor, Concentration Azotobacter sp 0 ml+10 liters waters (M0), 50ml+10 liters waters (M1), 100ml+10 liters waters (M2), 150ml+10 liters waters (M3), and 200ml+10 liters waters (M4). The results showed cocoa skin (B3) had an average height increase of 12.52 cm and an increase the number leaves of 8.07 strands, significantly different from treatment without organic matter (B0). The interaction of Azotobacter sp 200ml+10 liters waters (M4) concentration has an average height increase of 13.62 cm and the addition of leaves of 7.92 strands is significantly different from the consentration of Azotobacter sp 0ml+10 liters waters (M0). Azotobacter sp 200ml+10 liters waters (B3M4) gave the highest increase in average of 16.23 cm, number of leaves 9.33 strands, and 0.43 cm in diameter differed Azotobacter sp 0ml+10 liters waters (B0M0).Key Words : Teak, Organik Matter, Azotobacter